A review of the effect of 5-fluorouracil on the outcome of trabeculectomy in Ibadan (2004)
Aim: To retrospectively assess the outcome of trabeculectomy performed using an intraoperative sponge soaked in 5-fluorouracil (50 mg/ml). Methods: Trabeculectomy with an intraoperative sponge soaked with 5-f1uorouracil (5-FU) was performed in 21 eyes of 14 patients. The reduction in intraocular pressure (lOP), complications and variations in visual acuity were noted. Results: The mean preoperative lOP was 31.5 ± 10.6 mmHg. The mean postoperative lOP was 7.3 ± 5.7mmHg on the second postoperative day and 17.5 ± 9.8mmHg at 3 months. Postoperative complications were mostly transient, with 33% of eyes requiring postoperative antiglaucoma therapy to reduce lOP. Visual acuity Improved postoperatively in 3 eyes, worsened in 9 eyes and remained the same in 9 eyes. Conclusion: Even though a small study, an intraoperative sponge soaked with 5-FU seems to be a safe and effective adjunct to trabeculectomy.